Criminological Analysis of the Influence of Poverty in Increasing Crime in Cianjur - Amanda, Shakilla Nadya; Kuswandi, Kuswandi (Indonesian Journal of Law and Justice, 2025)
This study aims to analyze the influence of poverty on the increase of criminal behavior in Cianjur from a criminological perspective by examining how economic pressure and social constraints encourage individuals to engage in unlawful actions as a means to fulfill basic needs. The research focuses on identifying the factors that strengthen the link between poverty and crime, such as unemployment, limited access to education, income inequality, unstable family conditions, and weak social control in impoverished environments. A qualitative descriptive method was applied by utilizing secondary data from official reports, scientific literature, and statistical documents related to poverty and criminality in Cianjur. The data were analyzed through interpretive analysis to understand the correlation between social vulnerability and criminal behavior patterns. The results indicate that poverty significantly contributes to criminal activities including theft, fraud, robbery, motor vehicle theft, and juvenile delinquency, which are mostly economically driven offenses. Individuals experiencing persistent financial hardship tend to develop frustration and feelings of inequality, which increase the likelihood of crime. Moreover, social disorganization within poor communities creates opportunities for deviant behavior and exposure to negative peer influence. These findings align with strain theory and social disorganization theory, which emphasize that economic stress and disordered environments act as strong triggers for criminal behavior. The study concludes that efforts to reduce crime in Cianjur cannot rely solely on law enforcement but must be supported by poverty alleviation strategies, including improving education, expanding employment opportunities, empowering local communities, and enhancing overall social welfare to ensure sustainable crime prevention.